2008
DOI: 10.1136/jcp.2008.058073
|View full text |Cite
|
Sign up to set email alerts
|

Systemic mastocytosis with associated myeloproliferative disease and precursor B lymphoblastic leukaemia with t(13;13)(q12;q22) involvingFLT3

Abstract: Systemic mastocytoses represent neoplastic proliferations of mast cells. In about 20% of cases systemic mastocytoses are accompanied by clonal haematopoietic non-mast cell-lineage disorders, most commonly myeloid neoplasms. A case of systemic mastocytosis carrying the characteristic mutation at codon 816 (D816V) in the KIT gene of mast cells, with two concurrent accompanying clonal haematopoietic non-mast cell-lineage disorders, chronic myeloproliferative disease, unclassifiable and precursor B lymphoblastic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 9 publications
(10 reference statements)
1
20
0
Order By: Relevance
“…An example is lymphoid or biphenotypic (mixed) blast crisis in CML [90][91][92]. In rare cases, subclone formation from LSC may even result in the development of two histologically and cytogenetically unrelated, but still monoclonal neoplasms [92][93][94][95]. It has also been reported that hematopoietic neoplasms even produce a monoclonal microenvironment or a monoclonal microvasculature [96][97][98].…”
Section: Subclone Formation and Plasticity Of Lscmentioning
confidence: 99%
“…An example is lymphoid or biphenotypic (mixed) blast crisis in CML [90][91][92]. In rare cases, subclone formation from LSC may even result in the development of two histologically and cytogenetically unrelated, but still monoclonal neoplasms [92][93][94][95]. It has also been reported that hematopoietic neoplasms even produce a monoclonal microenvironment or a monoclonal microvasculature [96][97][98].…”
Section: Subclone Formation and Plasticity Of Lscmentioning
confidence: 99%
“…In such cases, the neoplastic mast cells and myeloid cells shared a common clonal origin and both harbored the activating KIT mutation [43]. There are infrequent reports of mastocytosis with additional lymphocytic neoplasia [44,45]. However, the activating KIT mutation was usually not detected in cells of the accompanying lymphocytic disease [44].…”
Section: Discussionmentioning
confidence: 99%
“…Review of the current literature shows that AHNMD primarily consists of myeloid malignancies—particularly acute myeloid leukaemia, chronic myelomonocytic leukaemia and chronic myelogenous leukaemia 5. There are rare reports of lymphoid neoplasms, including plasma cell dyscrasia,6 chronic lymphocytic leukaemia7 and B-lymphoblastic leukaemia,8 associated with SM. We now add to this list the rare occurrence of KIT D816V+ acute erythroid leukaemia (erythroid/myeloid type) as the AHNMD.…”
Section: Discussionmentioning
confidence: 99%